Islases celebrate 50th anniversary (Raton Range Raton, New Mexico, 1982)
Newspaper Article on the 50th Anniversary of Buster and Rosemae Huddleston.
Master list item #: 89
File location is in the Raton File Cabinet
Keywords: Islas, Felipe; Islas, Maria; Garcia, Cruz; Munoz, Enrigue; Carrera, Antonio; Carrera, Domitila; Islas, Salvador; Islas, (Mrs.); Gallardo, William; William, (Mrs.); Gonzalez, Dolores; Islas, Phillip; Ortiz, Abel; Ortiz, (Mrs.); Sandoval, John; Sandoval, (Mrs.); Islas, Frank; Islas, (Mrs.); Islas, Joe; Islas, (Mrs.); Islas, Isaac; Ortiez, Loretta; Nava, Francis; Garcia, Paul; Islas, Maria; Gallardo, David; Sanchez, Robert F; Sandoval, Eva; Gonzalez, Patricia; Islas, Norma; Islas, Antonia; Garcia, Ramon; Hernandez, Bucho; Garcia, Paul; Garcia, (Mrs.); Calderon, Narciso; Calderon, (Mrs.); Bloomenrader, Ramona; Patranovich, Marian; Patranovich, (Mrs.); Gonzalez, Arthur; Gonzalez, (Mrs.); Salazar, Emma; Lucero, Eufenia; Lucero, (Mrs.); Montoya, Flora; Montoya, (Mrs.); Leal, Jeff; Romero, Juanita; Baptist Catholic Church; St. Joseph's Catholic Church; VFW Hall; Local History; Biography; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico; Dawson, New Mexico